2008
DOI: 10.1007/s10592-008-9747-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex identification of northern ungulates using low quality and quantity DNA

Abstract: We evaluated PCR primer sets to determine the most effective technique for identifying sex of northern ungulates. We sought markers that required only a single pair of primers to amplify both X-and Y-linked alleles; that amplified X-and Y-linked products that were easily distinguishable using agarose gel electrophoresis; and that produced short amplicons amenable to amplification using DNA of poor quality and low quantity, as is often found in non-invasively collected samples such as feces. Primer pairs KY1/KY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
(26 reference statements)
0
21
0
Order By: Relevance
“…Unique genotypes obtained from DNA in noninvasively collected fecal pellets or hair samples can be used to identify individuals upon initial capture (i.e., identification via DNA) and recapture, enabling the pellet or hair samples to take the place of physically marked individuals. Fecal DNA also can be used to accurately differentiate sexes (e.g., Brinkman and Hundertmark , Ebert et al ) and assess sex ratios (e.g., before vs. after harvest; Pierce et al ). Lastly, the genotypic data generated in such approaches can be used for additional purposes, such as to evaluate genetic diversity or familial relationships (Waits and Paetkau , Yoshizaki , Colson et al ).…”
mentioning
confidence: 99%
“…Unique genotypes obtained from DNA in noninvasively collected fecal pellets or hair samples can be used to identify individuals upon initial capture (i.e., identification via DNA) and recapture, enabling the pellet or hair samples to take the place of physically marked individuals. Fecal DNA also can be used to accurately differentiate sexes (e.g., Brinkman and Hundertmark , Ebert et al ) and assess sex ratios (e.g., before vs. after harvest; Pierce et al ). Lastly, the genotypic data generated in such approaches can be used for additional purposes, such as to evaluate genetic diversity or familial relationships (Waits and Paetkau , Yoshizaki , Colson et al ).…”
mentioning
confidence: 99%
“…We collected 4-6 pellets for DNA analysis from each pellet group encountered on deer-trail transects. We followed sampling, DNA extraction, genotyping, and analysis protocols described in Brinkman et al (2010Brinkman et al ( , 2011. We resampled transects 2-8 times/annual field season (approx.…”
Section: Methodsmentioning
confidence: 99%
“…Feb-May) at 10-day intervals. During poor conditions (warm summer months with abundant rainfall), Brinkman et al (2010) found that pellets should be collected 10 days following deposition to yield sufficient DNA. Starting and ending date of sampling occasions was dependent on date of snowmelt and green-up.…”
Section: Methodsmentioning
confidence: 99%
“…A logical further step of this method is to use it for the determination of sex-specific browsing patterns. Some studies have determined sex from eDNA samples using traditional fragment-based methods [11,12]. Forensic applications have used single nucleotide polymorphisms (SNPs) for sexing samples, but fewer eDNA applications use SNPs.…”
Section: Introductionmentioning
confidence: 99%